Pay transparency and entrepreneurship - Shang, Longfei; Saffar, Walid (Journal of Banking & Finance, 2024)
Using the staggered adoption of U.S. state-level pay transparency laws that improve pay transparency, we find that the probability of high-wage workers becoming entrepreneurs significantly increases following the adoption of such laws. Moreover, the salaries of high-wage workers significantly increase following the laws’ passage. These findings are consistent with theory suggesting that improved pay transparency increases the relative return of entrepreneurship for high-wage workers.